Identification of robust controller for 3hp 3Φ induction motor - H. Sathishkumar; S. S. Parthasarathy (IAES International Journal of Robotics and Automation (IJRA), 2019)
This paper deals about the identification of robust controller for 3hp 3Φ induction motor which is used in cable industry (Ravicab cables private limited) at Bidadi. In this cable industry 3hp 3Φ induction motor is used for cable pulling purpose. This industry is using PID (Proportional derivative integral) controller based VFD (Voltage frequency drive) for controlling the speed of this 3hp 3Φ induction motor. This VFD is not functioning well for the non linear load and disturbance environment. Therefore in this paper Neural network based speed controller is proposed as proposed controller-I for replacing the PID based VFD. Performance of the 3hp 3Φ induction motor is estimated when Neural network controller is interfaced with the motor. Then Neuro-fuzzy controller based speed controller is proposed as proposed controller-II for replacing the PID based VFD. Performance of the 3hp 3Φ induction motor is estimated when Neuro-fuzzy controller is interfaced with the motor. At last robust controller for the 3hp 3Φ induction motor which is used for cable pulling purpose is going to be identified by doing comparison chart between Neural network and Neuro-fuzzy controller.